2015
DOI: 10.1097/ijg.0000000000000140
|View full text |Cite
|
Sign up to set email alerts
|

Latanoprost-induced Cytokine and Chemokine Release From Human Tenon’s Capsule Fibroblasts

Abstract: Latanoprost induced proinflammatory cytokine and chemokine release from HTFs in a manner dependent on MAPK and NF-κB signaling. These effects of latanoprost might influence bleb scarring after filtration surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…35 Using human orbital adipose tissue samples, they reported that bimatoprost upregulates pathways involved in the browning of adipocytes via MAPK, PI3/Akt, and p38. 35 In addition, LAT-A activated the MAPKs extracellular signal-regulated kinase, p38, and c-Jun NH 2 -terminal kinase, 36 indicating that FP agonist-induced PAP is also caused by browning of adipocytes via kinase pathways. In this study, we focused on the effect of OMD on adipogenesis and the regulation of its transcriptional factors (Pparg, Cebpa, and Cebpb) compared with those of FP agonists.…”
Section: Discussionmentioning
confidence: 99%
“…35 Using human orbital adipose tissue samples, they reported that bimatoprost upregulates pathways involved in the browning of adipocytes via MAPK, PI3/Akt, and p38. 35 In addition, LAT-A activated the MAPKs extracellular signal-regulated kinase, p38, and c-Jun NH 2 -terminal kinase, 36 indicating that FP agonist-induced PAP is also caused by browning of adipocytes via kinase pathways. In this study, we focused on the effect of OMD on adipogenesis and the regulation of its transcriptional factors (Pparg, Cebpa, and Cebpb) compared with those of FP agonists.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is worth noting the findings of Liu et al, who reported that latanoprost influenced bleb scarring after trabeculectomy. 24 …”
Section: Discussionmentioning
confidence: 99%
“…18 NF-jB is a key transcriptional activator of multiple proinflammatory cytokines, such as MMPs, IL-1b, and TNF-a. 20 As previously reported, 26 latanoprost can activate P38-NF-jB signaling pathways in human Tenon's capsule fibroblasts, which lead to increased production of inflammatory cytokines and chemokines. Similar to the previous report, 26 the present study showed that topical application of 0.005% latanoprost activated P38-NF-jB signaling pathways with increased production of inflammatory cytokines including TNF-a, IL-1b, MMP-3, and MMP-9 in conjunctiva.…”
Section: Discussionmentioning
confidence: 70%
“…20 As previously reported, 26 latanoprost can activate P38-NF-jB signaling pathways in human Tenon's capsule fibroblasts, which lead to increased production of inflammatory cytokines and chemokines. Similar to the previous report, 26 the present study showed that topical application of 0.005% latanoprost activated P38-NF-jB signaling pathways with increased production of inflammatory cytokines including TNF-a, IL-1b, MMP-3, and MMP-9 in conjunctiva. In addition, the present study showed that topical application of latanoprost increased CD4 þ T cells infiltration with increased production of IFN-c and IL-17A and decreased production of IL-13 in conjunctiva, which may be due to the consequence of activation of P38-NF-jB signaling and increased production of inflammatory cytokines in ocular surface.…”
Section: Discussionmentioning
confidence: 70%